Postcolonial Identity through Singlish Phonology through Film Dialogue in Global Media Analysis - Dan Fereth B. Fajardo; Nurvita Wijayanti; Aris Munandar; Tofan Dwi Hardjanto (PAROLE: Journal of Linguistics and Education, 2026)
Singlish, formally recognised as Singaporean Colloquial English (SCE), represents a distinct variety within the global landscape of World Englishes. This study investigates the segmental and suprasegmental features of Singlish through an Optimality-Theoretic framework (OT), utilising a proposed constraint hierarchy. Data comprising 600 phrases from four (4) high-frequency scenes were extracted from the film Crazy Rich Asians and processed via the corpus software AntConc. The OT analysis focuses on specific constraint rankings—including STRESS-INITIAL, FT-BIN, IDENT-STRESS, and NO-CODA—which are subsequently validated through acoustic analysis using Praat to determine if cinematic representations align with authentic phonological patterns. Beyond modelling, this research situates these linguistic systems within a broader framework, linking local patterns to postcolonial identity formation. The findings suggest that these features emerge from the interaction between local identities and global media, advancing the hypothesis that the film reflects a shift from Bhabha's mimicry toward During's perspective on cultural mediation.